The Relationship Between Social Media Use and Beliefs in Conspiracy Theories and Misinformation - Enders, Adam M.; Uscinski, Joseph E.; Seelig, Michelle I.; Klofstad, Casey A.; Wuchty, Stefan; Funchion, John R.; Murthi, Manohar N.; Premaratne, Kamal; Stoler, Justin (Political behavior, 2023)
Numerous studies find associations between social media use and beliefs in conspiracy theories and misinformation. While such findings are often interpreted as evidence that social media causally promotes conspiracy beliefs, we theorize that this relationship is conditional on other individual-level predispositions. Across two studies, we examine the relationship between beliefs in conspiracy theories and media use, finding that individuals who get their news from social media and use social media frequently express more beliefs in some types of conspiracy theories and misinformation. However, we also find that these relationships are conditional on conspiracy thinking––the predisposition to interpret salient events as products of conspiracies––such that social media use becomes more strongly associated with conspiracy beliefs as conspiracy thinking intensifies. This pattern, which we observe across many beliefs from two studies, clarifies the relationship between social media use and beliefs in dubious ideas.